Research on the Impact of Environmental Protection Tax on Green Technology Innovation of Enterprises - Kang, Wenzhi (Transactions on Economics, Business and Management Research, 2024)
The environmental protection tax reform implemented since January 1, 2018, occupies a significant position in China’s environmental policy framework, and also marks a key practice of China’s ecological and environmental protection tax in the new era. It is an important feature of the domestic environmental regulation policy system and an important measure for the implementation of China’s ecological and environmental protection tax law in the new era. Against the backdrop of promoting high-quality domestic development strategies, how does this policy affect the motivation to stimulate green technological innovation and what effects does it have on the quantity and quality of green innovation behavior in society as a whole? This study selected A-share listed companies listed on the Shanghai and Shenzhen stock markets from 2014 to 2020 as samples, and used the promotion of environmental protection tax system as a quasi natural experimental scenario. A double difference model was used for empirical analysis to explore the specific impact of environmental protection tax system on the innovation of green technology in enterprises. The research results indicate that the reform of the environmental tax system effectively motivates enterprises to take action in green innovation and improves the quality of their innovation. These research conclusions can provide suggestions and theoretical basis for deepening environmental tax reform, building a market-oriented green technology innovation system, and forming a high-quality innovation intellectual property system.